Faces of a Face - Kisonová, Renáta (Peter Lang GmbH, 2021)
The book focuses on face and portraiture regarding philosophical, aesthetical, cognitive, and anthropological attitudes. It represents the author's research on portrait recognition. She shows 11 portraits to study participants, while monitoring them with an eye tracker.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Gesicht; Philosophie; Kognition; Ästhetik; Semantik; Metapher; Bildnismalerei; Porträtfotografie